2023
DOI: 10.1111/nph.18971
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary responses of life‐history strategies to climatic variability in flowering plants

Abstract: Summary The evolution of annual or perennial strategies in flowering plants likely depends on a broad array of temperature and precipitation variables. Previous documented climate life‐history correlations in explicit phylogenetic frameworks have been limited to certain clades and geographic regions. To gain insights which generalize to multiple lineages we employ a multi‐clade approach analyzing 32 groups of angiosperms across eight climatic variables. We utilize a recently developed method that accounts f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 101 publications
1
4
0
Order By: Relevance
“…Conversely, at high elevation, a life cycle characterized by reduced annual reproduction and allocation of resources to self-maintenance constitutes a better strategy under a short growing season and limited resources (Childs et al ., 2010; Johnstons & Pickering, 2004; Milla et al ., 2009). In fact, the alternative life history strategies expressed by our two genotypes at contrasting elevations are in line with observed differences in species occurring along elevation gradients, where short lived species with high reproductive investment are typical at lower elevations and long lived species with enhanced offspring quality and bet hedging strategies predominate at high elevation (Boyko et al ., 2023; Laiolo & Obeso, 2017).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Conversely, at high elevation, a life cycle characterized by reduced annual reproduction and allocation of resources to self-maintenance constitutes a better strategy under a short growing season and limited resources (Childs et al ., 2010; Johnstons & Pickering, 2004; Milla et al ., 2009). In fact, the alternative life history strategies expressed by our two genotypes at contrasting elevations are in line with observed differences in species occurring along elevation gradients, where short lived species with high reproductive investment are typical at lower elevations and long lived species with enhanced offspring quality and bet hedging strategies predominate at high elevation (Boyko et al ., 2023; Laiolo & Obeso, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…We interpret this evidence as a trade-off triggered by the environmental conditions in the low elevation environment which causes high elevation plants to exceeded allocation of resources to reproduction, thus compromising their physiological ability to survive the following winter. In line with other species occurring along elevational gradients, size in D. carthusianorum is thus better interpreted as a divergent phenotypic trait exhibiting spatially plastic variation that feedbacks on key fitness components rather than a fitness proxy per se (Bonser & Aarsen, 2009; Cheplick, 2020; Boyko et al ., 2023; Halbritter et al ., 2018; Körner 2003, Midolo et al, 2020). Overall, our results suggest that adaptive genetic variation regulating trade-offs between fitness components of genotypes mediate adaptation in D. carthusianorum .…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The traditional plant life form classification (Raunkiaer, 1934) has been commonly used as a proxy to plant strategies, allowing to test hypotheses regarding the relationship between habitats and plant traits (Schulze, 1982;Irl et al, 2020;Shary et al, 2020;Boyko et al, 2023). This classification summarizes structural and functional traits that indicate habitat preferences and ecological and resistance plant strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Associations between plant life forms and habitats with varying resource availabilities and disturbance intensity have also been observed at the macroevolutionary scale. For instance, a recent multi-clade analysis revealed that annual life forms more often evolve in habitats prone to extreme heat (Boyko et al, 2023). Similarly, the evolution of annual life forms among Oenothera species is associated with the occupation of arid regions (Evans et al, 2005).…”
Section: Introductionmentioning
confidence: 99%